Freshwater conservation potential of protected areas in the Tennessee and Cumberland River Basins, USA. (June 2016) - Thieme, Michele L.; Sindorf, N.; Higgins, J.; Abell, R.; Takats, J. A.; Naidoo, R.; Barnett, A.
Abstract: The ability of existing protected areas (PAs) to conserve freshwater species and ecosystems has been little investigated. In this study the freshwater conservation potential of PAs was evaluated based on their geospatial attributes and spatial relationship to threats. Specifically, the following questions were addressed: (a) to what extent, if any, do PA drainage network location and size affect the potential of PAs to conserve freshwater species and habitats within them?; (b) how are the factors that limit or promote conservation potential distributed in relation to PAs across a region?; and (c) what are the broader implications for how PAs can be designed and managed to contribute to freshwater conservation around the world? Eight factors that affect freshwater conservation potential for 297 PAs within the Tennessee and Cumberland River Basins (US) were analysed. Four of these attributes (connectivity, impervious surface area, agricultural land cover, and upstream storage) showed enough variation across PAs such that the effect of PA size, drainage network position, and their interaction on those attributes, was able to be modelled. The results support the hypothesis that PA drainage network location and size affect freshwater conservation potential of PAs. Both have a statistically significant effect on each of the four conservation potential attributes, either as a main effect, or through an interaction, although the direction of these relationships is not always intuitive. Of the factors that limit or promote conservation potential, PAs appear to be most often affected by land conversion to agriculture and a loss of connectivity. This study underscores the importance of PA managers understanding key internal and external threats so that they can take mitigating or minimizing action, and the need to define PA locations and boundaries within a larger basin context. Copyright © 2016 John Wiley & Sons, Ltd.